2010
DOI: 10.1007/s10067-009-1358-x
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment with tacrolimus of progressive interstitial pneumonia associated with amyopathic dermatomyositis refractory to cyclosporine

Abstract: A 58-year-old male was admitted to our hospital because of periungual nailfold an erythema and erythematous rash on the dorsal joints of his hands and feet, but no muscle weakness. He was thus diagnosed to have amyopathic dermatomyositis. He had moderate hypoxemia and his chest computed tomography scans demonstrated bilateral ground-glass opacities, implicating complication with interstitial pneumonia. Therapy was initiated with pulsed methylprednisolone followed by high-dose corticosteroids, pulsed cyclophosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 13 publications
0
24
0
Order By: Relevance
“…All patients received corticosteroids combined with another immunosuppressant, but without standard treatment regimen. Evidences indicate that calcineurin inhibitors including cyclosporin A and tacrolimus are efficacious in CADM [19,20]. In order to analyze the potential difference between calcineurin inhibitors and noncalcineurin inhibitors, we categorized CADM patients into two groups according to treatment regimen with or without calcineurin inhibitors.…”
Section: Increases Of Serum Il8 In Cadm Patients With Active Ildmentioning
confidence: 99%
“…All patients received corticosteroids combined with another immunosuppressant, but without standard treatment regimen. Evidences indicate that calcineurin inhibitors including cyclosporin A and tacrolimus are efficacious in CADM [19,20]. In order to analyze the potential difference between calcineurin inhibitors and noncalcineurin inhibitors, we categorized CADM patients into two groups according to treatment regimen with or without calcineurin inhibitors.…”
Section: Increases Of Serum Il8 In Cadm Patients With Active Ildmentioning
confidence: 99%
“…Wilkes et al [20] reported that DM/PM patients with refractory or severe IP were successfully treated with tacrolimus. Recently, Ando et al [21] reported a case of ADM and CyA-resistant IP that was treated successfully with tacrolimus.…”
Section: Discussionmentioning
confidence: 98%
“…However, to our knowledge, this is the first report to document the effectiveness of tacrolimus for LD-CTD histopathologically showing a chronic fibrotic interstitial pneumonia pattern, a type of ILD that is more refractory to pharmacologic therapy. Previous studies (13) have shown the BALF lymphocyte count to increase in ILD patients with ADM who have been successfully treated with TAC. In the present case, the BALF lymphocyte count was also increased.…”
Section: Discussionmentioning
confidence: 99%
“…The immunosuppressive mechanisms of tacrolimus are reported to be similar to those of CsA, although the activity of the former is approximately 30-100-fold more potent than that of the latter in vitro (11). Several reports have documented the successful use of tacrolimus for cases of polymyositis/ dermatomyositis (PM/DM) or amyopathic dermatitis (ADM)-associated ILD that are refractory to treatment with corticosteroids in combination with CsA and/or cyclophosphamide (12)(13)(14). However, to our knowledge, this is the first report to document the effectiveness of tacrolimus for LD-CTD histopathologically showing a chronic fibrotic interstitial pneumonia pattern, a type of ILD that is more refractory to pharmacologic therapy.…”
Section: Discussionmentioning
confidence: 99%